Effectiveness of Project-Based Learning in Enhancing Creativity among Vocational Students in Islamic Boarding School Contexts - Hartini Ramli; Andi Yasir Amsal; Muh . Bhilal Halim; Sudarmanto Jayanegara (Information Technology Education Journal, 2025)
This reserach aims to examine the effectiveness of implementing the Project-Based Learning (PJBL) model in enhancing the students’ creativity at vocational high schools (SMK) with a Islamic Boarding School context system, specifically at SMKS Islam Pesantren Alam Indonesia. Vocational education, particularly within Islamic Boarding School context SMKS, often emphasizes the development of technical skills; however, the main challenge lies in how to also cultivate the students’ creativity. Using a quantitative approach with a descriptive quantitative design, this research explores the relationship between the implementation of the PJBL model and the enhancement of the students’ creativity. Data were collected through questionnaires that measured the students’ creativity across four main dimensions: fluency, flexibility, originality, and elaboration. The results show that the implementation of the PJBL model has a significant impact on the students’ creativity at SMKS Islam Pesantren Alam Indonesia. Regression analysis revealed that each application of the PJBL model is estimated to increase the students’ creativity by 8.952 points. The t-test results also indicated a very low significance value (p < 0.05), confirming that the influence of the PJBL model on the students’ creativity is statistically significant. The most prominent dimension of creativity observed was fluency, followed by flexibility, originality, and elaboration—all of which fell within the "Good" category. This study reinforces the evidence that the PJBL model is effective in developing the students’ creativity, which is crucial for their competitiveness in an increasingly demanding job market. Additionally, this research is expected to provide new insights into curriculum development and more relevant teaching methods for Islamic Boarding School context vocational schools, as well as serve as a reference for educators and policymakers in designing more innovative and applicable learning strategies